2004
DOI: 10.1111/j.1365-2648.2004.03069.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in nursing work

Abstract: In this work it is shown that the effectiveness of operator's activities is higher in individuals with medium emotional intelligence than in those with low emotional intelligence. It is achieved due to the greater expression of the alpha rhythm for 69 % in amplitude and for 78 % in the index, low-frequency beta-rhythm amplitude for 50 %, lower expression of the delta-rhythm in the index for 22 % at rest. In addition, the group with medium emotional intelligence compared to the group with low emotional intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
269
0
31

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(308 citation statements)
references
References 44 publications
8
269
0
31
Order By: Relevance
“…In their study among student nurses, McCabe et al (2005), found that the most important reasons to choose the profession were (1) to help others; (2) to do interesting and challenging work; and (3) to work closely with people in need. Moreover, according to McQueen (2004), nurses enjoy the benefits from emotional work because they are satisfied with engaging with patients at a personal level. Being a nurse brings the opportunity to help others and make a difference in their lives (Morgan & Lynn, 2009).…”
Section: Emotional Demands Motivation and Well-being In Nursing Profmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study among student nurses, McCabe et al (2005), found that the most important reasons to choose the profession were (1) to help others; (2) to do interesting and challenging work; and (3) to work closely with people in need. Moreover, according to McQueen (2004), nurses enjoy the benefits from emotional work because they are satisfied with engaging with patients at a personal level. Being a nurse brings the opportunity to help others and make a difference in their lives (Morgan & Lynn, 2009).…”
Section: Emotional Demands Motivation and Well-being In Nursing Profmentioning
confidence: 99%
“…Continued exposure to these 4 demands is associated with stress, burnout and fatigue (Garrosa et al, 2008;Winwood et al, 2006), among other mental and physical problems. Nevertheless, helping others and working closely with people in need is a great source of motivation for nurses, which can also have many benefits (McCabe et al, 2005;McQueen, 2004). The desire to care for others and offering compassion are often motives to choose nursing profession and form part of the "ideal of nurse" that usually focuses on caring.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of EI for the purposes of career selection and job orientation has become a common practice in a great number of organizations, and according to a recent survey of benchmark practices in the United States, 80% of the major corporations are now trying to promote EI in their organization (Zeidner et al, 2004). In line with this enthusiasm, studies investigating EI in the nursing context are currently a topic of keen interest (Gerits, Derksen, Verbruggen, & Katzko, 2005;Kooker, Shoultz, & Codier, 2007;Landa, Lopez-Zafra, Martos, & Guilar-Luzon, in press;Mcqueen, 2004;Montes-Berges & Augusto, 2007).…”
mentioning
confidence: 99%
“…Hastalar ile iyi bir ilişki kurabilmeleri için hemşirelerin duygularını tanıyan ve yöneten, empati yapabilen, kendi kendini motive edebilen, empati gücü yüksek ve etkili bir şekilde iletişim kurabilen, bir başka deyişle duygusal zeka becerileri gelişmiş bireyler olmaları gerekmektedir (Avşar ve Kaşıkçı, 2010;Kuzu, 2008;Ünsar, Fındık, Sadırlı, Erol ve Ünsar, 2009). Günümüzde hemşirelik hizmetlerini yürütürken, doğrudan hasta bakımı gereksinimlerini karşılamak ve çok disiplinli bir ekip ile işbirliği içinde çalışabilmek için duygusal zekâ becerilerinin kullanımına gerek olduğu belirtilmektedir (McQueen, 2004).…”
Section: Hemşirelik Eğitiminde Duygusal Zekâunclassified
“…Bu kavramın bakış açısına göre, duygusal zekâ yeteneklerine sahip olan birey, zihinsel ve duygusal olarak istikrarlı, duygusal anlamda yetenekli, duygusal ve sosyal işlevlerini yerine getirebilen bir birey olarak düşünülür (Mayer, DiPaolo ve Salovey, 1990). İletişim becerisi ve duygusal zekâ konuları hemşirelik eğitiminde ele alınması gereken konular arasında görülmektedir (McQueen, 2004;Suikkala ve Leino-Kilpi, 2001). …”
Section: Introductionunclassified